Anchoritic Traditions of Medieval Europe - Liz Herbert McAvoy (Boydell Press, 2010)
This is a survey volume which examines the different traditions of religious solitary enclosure in western Europe during the Middle Ages. It contains work by leading Continental academics which had not been accessible to an English-speaking audience before this book's publication. The essays contained within this volume also allow for the first time a comparative approach to medieval anchoritism in western Europe during the period under scrutiny.